La psicología en la Terapia Intensiva - Pacios Dorado, Juan Leonardo; Barroso Fontanals, Miguel Enrique (Revista científica estudiantil 2 de Diciembre, 2023)
Sr. Editor: The use of psychology in patients admitted to Intensive Care is of vital importance to both their emotional well-being and physical recovery. Intensive Care is a hospital unit that cares for patients with serious illnesses or injuries that require constant monitoring and care. Patients in Intensive Care often face extreme stress, pain, uncertainty and isolation. Serious medical conditions, the presence of numerous devices and the lack of contact with loved ones can generate feelings of anxiety, distress, fear and depression in patients(1). In this context, psychologists play an important role in providing emotional support, alleviating distress, and helping patients cope with the negative emotions that may arise during their hospitalization in this service. In addition, psychological intervention can be beneficial in preventing and managing the trauma associated with the experience of being in this medical unit. Psychologists work closely with the medical team to assess and address patients’ emotional needs. They use therapeutic techniques that include active listening, emotional support, relaxation and breathing techniques, guided visualization and cognitive restructuring, among others. These interventions help to reduce anxiety, improve mood, promote acceptance of the situation and strengthen patients’ psychological resources(2). In addition to direct support for patients, psychologists should also provide support for family members and caregivers. Hospitalization in this inpatient service can be overwhelming for both patients and their loved ones, and psychological support can be critical in managing stress, worry and adjustment to the situation(3). Importantly, the use of psychology in Intensive Care is not limited to emotional support alone, but can also play a role in ethical decision making and in planning the patient’s transition to other care units or home. Psychologists can help patients and their families make informed decisions and emotionally process difficult situations related to treatment and medical prognosis. The use of psychology in intensive care inpatients is essential for the emotional well-being and recovery of patients. Psychologists provide emotional support, stress management and ethical decision making to both patients and their families. Their intervention contributes to improving patients’ quality of life and promoting comprehensive care in this challenging medical environment.